Police civilianization and the production of underclass violence: the case of para-police Chengguan and street vendors in Guangzhou, China - Xu, Jianhua (The British journal of criminology, 2019)
Using data collected from systematic social observation, participant observation, interviews, and content analysis of media reports in Guangzhou, this article studies violent confrontation between China’s para-police chengguan (urban management officers) and street vendors. We find that most violent confrontations occur between street vendors and civilian staff—auxiliary chengguan—rather than between street vendors and sworn officers—official chengguan. We further reveal that the unequal power structure within the chengguan system shapes the division of labour between official chengguan and auxiliary chengguan, resulting in most of the ‘dirty work’ of street-level law enforcement being conducted by the latter, the second-class staff in the system. The research contributes to our understanding of pluralised policing and how police civilianization affects a convergence of violence within the underclass as both auxiliary chengguan and street vendors are recruited from urban poor.